Transfer pricing: a comparison of the German and the South African system - Brodbeck, Jens (Centre for Law and Society, 2026)
The role of multinational enterprises (MNEs) in world trade has increased dramatically over the last 20 years. This in part reflects the increased integration of national economies and technological progress, particularly in the area of communications. The growth of MNEs presents increasingly complex taxation issues for both tax administrations and the MNEs themselves since separate country rules for the taxation of MNEs cannot be viewed in isolation but must be addressed in a broad international context." These are the first few words of the Preface of the 1996 Update to the OECD Report ,,Transfer Pricing Guidelines for Multinational Enterprises and Tax Administrations". This trend towards globalisation, together with South Africa's re-entry into the international economic community has lead to a significantly increasing demand for international tax planning by South African businesses. One of the most controversial, and often least understood, issues of international tax planning, concerning multinational enterprises, is that of Transfer Pricing.